Student-Athlete Non-Academic Performance in Sport Faculty - Nuryadi Nuryadi; Jajat Darajat Kusumah Negara; Agus Gumilar; Burhan Hambali; Tri Martini; Eko Purnomo; Nur Khois Jajiyah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study is to examine student-athlete non-academic performance in the sports faculty. Research on the topic has highlighted the complex interplay between student athletes' identities as athletes and scholars. The author surveyed 319 student-athletes in the sports faculty environment of the Indonesia University of Education. The survey was conducted using the non-cognitive factors affecting student-athlete performance, which include three major indicators such as perceptions of student-athletes from faculty, peers, and the student-athletes themselves; academic experiences of a student-athlete; and awareness of influencing factors. The results show that student-athletes' non-academic performance is in the fair category. The three dimensions show a grade point average of 3.08 for the academic experiences of a student-athlete dimension, 3.19 for the awareness of influencing factors dimension, and 3.14 for the perceptions of student-athlete indicators from faculty, peers, and the student-athlete. Regression analysis shows the contribution of each dimension of non-academic performance of student athletes, showing a relative contribution of 35% perceptions from faculty, peers, and the student athlete, 30% academic experiences, and 35% awareness of influencing factors. The study's findings demonstrate that student athletes' nonacademic performance in sports faculties has negative effects. This condition becomes a challenge for educational institutions to create a special academic arrangement for student-athletes; the continuity of a non-academic situation must be designed to support their academic performance.